Gorkha Women as Forgotten Heroes in the Gorkha War Narratives - Rai, Ram Prasad (Pursuits: A Journal of English Studies, 2024)
This paper aims to focus on how Gorkha women are left behind the curtain in terms of their role in the war history where their male Gorkhas’ bravery only is prioritized. When we turn the pages of the Anglo-Nepal Wars (1814-1816), the writers confidently say that the Gorkha warriors are back supported by women as well as children. However, they are shadowed by the description of the ferocious war performance of male Gorkha warriors such as Bir Bala Bhadra Kunwar, Amar Singh Thapa, Bhakti Thapa and so on. The only question is who the women warriors there are to support them attacking the English troops. Similarly, the Gorkhas serve the British Army and fight for Britain. For a long period during wars, they do not return home. During their service period, their wives remain at home to run all the family affairs such as raising children, caring the old parents, and cultivating land. The wives of those who die, get injured, and go missing have a burden of running family economy. They are compelled to keep all things well in the family. So, are not the Gorkha women as heroes as their male folks? The answer is sure to be- ‘Yes, they are’. This paper will certainly help future researchers in the area and also the government to manage new rules and concepts regarding Gorkha issues.